THE APPLICATION OF EDUCATIONAL SNAKE AND LADDERS (ULTRASI) AND SMART CARD LEARNING MEDIA IN INCREASING STUDENT ACTIVENESS - Mar'ah, Umrotul; Ismaya, Erik Aditia; Pratiwi, Ika Ari (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis research aimed to determine and analyze the activeness level of 6th grade students of SDN 2 Bategede in learning activities through the use of ULTRASI media (Educational Snakes and Ladders) and Smart Cards. This classroom action research was conducted at SDN 2 Bategede with the research subjects of 33 students in 6th grade. Data collection techniques include interviews, observation sheets and questionnaires, and documentation. The data analysis used is qualitative and quantitative. The results showed that the application of Educational Snakes and Ladders (ULTRASI) and smart cards had not succeeded in increasing student activeness based on the questionnaire and were successful based on observation with an average observation score of 84% and an average questionnaire score of 78%. The failure to achieve the research success indicators on the questionnaire may occur due to the lack of guidance of researchers in explaining the contents of the questionnaire to students. In cycle II, questionnaires and observations showed that the application of Educational Snakes and Ladders (ULTRASI) and smart cards was sucessful to increase student activity with an average observation score of 96% and an average questionnaire score of 82%. Keyword: Educational Snake Ladder; Smart Card; Student Activeness